The Psychological Impact of Social Media on Adolescents - Kumar, Rima M. (AG Volumes, 2025)
Concerns over social media’s potential effects on users’ psychological health have grown as its usage has increased. Online social media, which has become an integral part of our everyday lives, is held responsible for the rise in mental health issues among younger people. The purpose of this article is to review the diverse literature that has been conducted on the psychological effects of social media on adolescents. This review highlights both the positive and negative psychological impacts of social media on adolescents. While social media offers opportunities for learning, connection, entertainment, and income generation, it also contributes to addiction, cybercrime, anxiety, and the erosion of cultural values. The influence on adolescents’ self-esteem and mental health is significant, with time spent, activity type, emotional investment, and addiction closely linked to psychological distress. Despite existing studies, many mediating and moderating factors remain under-explored. The findings emphasize the need for comprehensive educational programs, tailored interventions for cyberbullying, and balanced policies that promote healthy, supportive digital engagement for adolescents.